Sexuality in Folktales: Asset or Liability to Socialisation of Learners in Zimbabwean schools - Taringa, Beatrice (HTS teologiese studies, 2023)
The portrayal of sexuality in folktale course-books that are prescribed for secondary school learners in Zimbabwe is indeed a cause for concern. Not much attention, if any, has been given to exploring the portrayal of ‘sexuality’ especially in ChiShona prescribed course-books. This article qualitatively explored through content and discourse analysis the portrayal of ‘sexuality’ in folktales prescribed course-books based on an Afrocentric perspective of Unhu and Ubuntu. The study sought to determine whether course-books are an asset or a liability for the socialisation of learners of both genders especially at the critical adolescence stage of development. This undertaking assessed gender attributes, norms, values, and behaviour patterns proffered in school course-books. The examination of the ‘sexuality’ portrayed in these course-books was based on the assumption that education is value-laden. The gender value inherent in these course-books being a vaccine for the social ills like gender inequalities bedevilling Shona communities. The major finding was that the portrayal of ‘sexuality’ in the course-books analysed in this study shows that they are more of a liability. The article recommended a gender discourse that evaluates and critically analyses the gender portrayals in the course-books to avoid losing the gender equality milestones achieved so far in Zimbabwe.Contribution: The study examined sexuality sensibilities secondary school learners are exposed to through the authority of folktale prescribed course-books: Hodza’s (1983) Ngano Dzamatambidzanwa and Fortune’s (ed. 1983) Ngano Volume 4. It adopted the Afrocentric perspective of Unhu and Ubuntu to assess the impact of these instructional materials on the learners’ socialisation processes.